2021
DOI: 10.3389/fmars.2021.526092
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Sea Ice Hypothesis: Trophic Interactions Among Breeding Pygoscelis Penguins With Divergent Population Trends Throughout the Western Antarctic Peninsula

Abstract: We evaluated annual and regional variation in the dietary niche of Pygoscelis penguins including the sea ice-obligate Adélie penguin (Pygoscelis adeliae), and sea ice-intolerant chinstrap (Pygoscelis antarcticus) and gentoo (Pygoscelis papua) penguins, three species that nest throughout the western Antarctic Peninsula (AP) to test the sea ice trophic interaction hypothesis, which posits that penguin breeding populations with divergent trends, i.e., declining or increasing, are reliant on differing food webs. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Adélies are ice‐obligate in winter, and previous work has suggested that declines in winter sea ice trigger declines in Adélies (Fraser et al 1992; Forcada and Trathan 2009; Gorman et al 2021). Therefore, we examined whether availability of sea ice could explain cycling in Adélie populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adélies are ice‐obligate in winter, and previous work has suggested that declines in winter sea ice trigger declines in Adélies (Fraser et al 1992; Forcada and Trathan 2009; Gorman et al 2021). Therefore, we examined whether availability of sea ice could explain cycling in Adélie populations.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling work has suggested that more fish in the diet promotes Adélie chick growth and survival (Chapman et al 2011), but existing empirical work exploring this hypothesis is limited. Research spanning the summers of 2008-2010 found that chicks located at a more southern colony on the western Peninsula, where they were provisioned with a higher trophic level diet (i.e., a greater ratio of fish to krill), had higher fledging weights than chicks around Anvers Island (Gorman 2015). However, within each site, the proportion of fish in the diet had no relationship with chick fledging weight.…”
Section: Decadal-scale Changes and Climate Changementioning
confidence: 98%
“…Adeĺie penguins (Pygoscelis adeliae) are a key indicator species under CEMP because they are important consumers of krill (Croxall et al, 2002). However, since the establishment of CEMP, there is increasing recognition Adeĺie penguin diets are more diverse than traditionally believed, with substantial spatial and temporal variability in the proportion of krill and fish consumed (Clarke et al, 2002;Ainley et al, 2003;Lynnes et al, 2004;Tierney et al, 2009;Gorman et al, 2021). The diet of Adeĺie penguin populations in the Scotia Sea, East Antarctic and regions of the Antarctic Peninsula are generally dominated by krill, while populations in the Ross Sea have a more varied diet and (Ribic et al, 2008) consume a mixture of fish and euphausiid species (Ratcliffe and Trathan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it might be expected that seabird populations would be particularly resilient to variation in the marine environment. However, seabirds are among the most threatened vertebrates (Dias et al, 2019), and a large literature has documented changes in demographic rates, abundance, or community structure with ocean climate variability (La Cock, 1986;Ainley et al, 1994;Montevecchi and Myers, 1997;Gjerdrum et al, 2003;Morrison et al, 2011;Oro, 2014;Gorman et al, 2021) with recent reports of mass mortality events in association with extreme marine heatwaves (Jones et al, 2018;Jones et al, 2019;Piatt et al, 2020;Arimitsu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%